Measuring Accounting Asset Informativeness - Chen, Qi; Schipper, Katherine; Zhang, Ning (The Accounting Review, 2022)
ABSTRACT We develop and validate an empirical measure of the informativeness of accounting assets in measuring firm-specific economic capital, an important determinant of both cash flows and intrinsic values. Our validation tests show that the asset informativeness measure is sensitive to differences in both accounting methods and implementation decisions at the firm level and corresponds to the way equity investors use the information in accounting assets. We find that accounting assets contain substantial information about firms' productive capacity (economic capital) and the information is not summarized in several earnings attributes often associated with earnings quality. JEL Classifications: M41; G14; G32.